ANALISIS GEOTEKNIK DAN KESTABILAN LERENG TOWER SUTT PT. PLN (Studi kasus: TW. 203 Pembangunan T/L 150 KV GI KAMBANG – GI TAPAN): ANALISIS GEOTEKNIK DAN KESTABILAN LERENG TOWER SUTT PT. PLN (Studi kasus: TW. 203 Pembangunan T/L 150 KV GI KAMBANG – GI TAPAN) - Kukuh Kurniawan Dwi Sungkono; Arbianto, Reki; Pande, Made Eka Prayuda; Gunarso, Gunarso (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2024)
Slope instability is caused by several lithological and structural factors, slope geometry, relative relief, ground water, as well as changes in use and land cover. Mountainous areas, development and expansion of infrastructure networks can inadvertently cause natural slope shifts, thereby negatively impacting the stability of the excavated slope. Analysis of the geotechnical properties of soil and rock is important for understanding and predicting the possibility of landslides at certain locations. Geotechnical analysis is needed to carry out slope stability analysis which is carried out using GEO5 software. Construction of T/L 150 KV GI Kambang – GI Tapan, Tower TW. 203 with a tower structure at the top of the slope. Based on these conditions, a comprehensive study is needed to analyze the stability of natural slopes due to tower loads. Soil Type, Parameters c' and ?' (Drained), Parameters Cu and ? (Undrained) and soil properties index are based on CPT test results. The Bishop, Spencer, Janbu and Morgenstern-Price methods on natural slopes, tower loads, Natural with Tower+Pile Loads, Natural Slopes with Tower+Pile Loads, Earthquake Loads produce a safe condition against failure in Short-Term (Construction) and Long-Term conditions. Term (Operational). Analysis of the Fellenius method on natural slopes and tower loads in Short-Term (Construction) and Long-Term (Operational) conditions shows unsafe conditions. The safety factors resulting from the Bishop, Spencer, Janbu and Morgenstern-Price methods do not show significant differences in values.